2010
DOI: 10.1111/j.1399-0012.2010.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance cholangiopancreatography for the accurate diagnosis of biliary complications after liver transplantation: comparison with endoscopic retrograde cholangiography and percutaneous transhepatic cholangiography – long‐term follow‐up

Abstract: Biliary complications after liver transplantation remain a serious cause of morbidity and mortality. Direct invasive cholangiographic techniques, endoscopic retrograde cholangiography (ERCP) or percutaneous transhepatic cholangiography (PTC), have procedure-related complications. Magnetic resonance cholangiopancreatography (MRCP) is non-invasive, safe, and accurate. The aim of this study was to evaluate MRCP in detecting biliary complications following liver transplantation and comparing findings with ERCP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 18 publications
2
27
0
1
Order By: Relevance
“…In the case of positive MRC, the post-test probability of BC reaches 80% and 94%, respectively, whereas in the case of negative MRC, the post-test probability reduces to 1% and 4%, respectively. These estimates emphasize the results of previous direct comparison between MRC, ERC and PTC [54] , suggesting that the strength of MRC is represented by the large negative predictive value (94.4%), which is of help in excluding BC and avoiding unnecessary invasive procedures in patients with clinical low-to-moderate risk of BC [54] . Unfortunately, several methodological flaws affect the studies included in the above systematic reviews, including small sample size, uncertainty in clinical criteria defining the suspicion for BC, verification bias given the heterogeneity in the standard of reference tools and absence of a standardized MRC technique [1,55] .…”
Section: A B Csupporting
confidence: 74%
See 1 more Smart Citation
“…In the case of positive MRC, the post-test probability of BC reaches 80% and 94%, respectively, whereas in the case of negative MRC, the post-test probability reduces to 1% and 4%, respectively. These estimates emphasize the results of previous direct comparison between MRC, ERC and PTC [54] , suggesting that the strength of MRC is represented by the large negative predictive value (94.4%), which is of help in excluding BC and avoiding unnecessary invasive procedures in patients with clinical low-to-moderate risk of BC [54] . Unfortunately, several methodological flaws affect the studies included in the above systematic reviews, including small sample size, uncertainty in clinical criteria defining the suspicion for BC, verification bias given the heterogeneity in the standard of reference tools and absence of a standardized MRC technique [1,55] .…”
Section: A B Csupporting
confidence: 74%
“…For instance, some authors [47] have hypothesized that reduced biliary dilatation following post-OLT strictures might limit the accuracy of MRC. Detractors of MRC also argue that, although MRC correlates well with direct cholangiography procedures (P = 0.01) [54] , the examination delays the diagnosis when interventional ERC or PTC are finally needed. This is why the use of MRC still depends on local preferences based on availability, expertise and costs.…”
Section: A B Cmentioning
confidence: 99%
“…However, a prospective study of MRCP and ERC revealed comparable sensitivities for detection of biliary obstruction (13). Other studies confirmed a ≥90% sensitivity and specificity and positive and negative predictive values of 90% for MRCP (14,15). A normal MRCP therefore might avoid further invasive measures.…”
Section: Diagnosis Of Biliary Complicationsmentioning
confidence: 98%
“…Nevertheless, US with Doppler should be the initial modality for the evaluation of major vascular complications (e.g., hepatic artery thrombosis), which require urgent management. Magnetic resonance cholangiopancreatography (MRCP) has replaced ERCP as a noninvasive diagnostic modality for suspected post-LDLT biliary strictures, because its sensitivity and accuracy in the evaluation of biliary complications following transplantation are comparable to those of ERCP [45,46]. Unnecessary ERCP can be avoided in LDLT recipients when there is no evidence of biliary strictures on MRCP [47].…”
Section: Diagnosis Of Biliary Strictures After Ldltmentioning
confidence: 99%